PENGEMBANGAN BUKU KONSEP MATEMATIKA POKOK BAHASAN DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA MATERI BANGUN RUANG - Putriani, Ayu; Syafitri, Fatrima Santri (Universitas Batanghari Jambi, 2026)
This study aims to develop a mathematics concept book based on Problem Based Learning (PBL) on spatial geometry material to improve students' understanding. The method applied is Research and Development (R&D) using the Plomp model through three stages, namely initial investigation, prototype development, and evaluation. The mathematics concept book was then validated by a number of experts, including material, media, and language experts. The validation results showed that the mathematics concept book was included in the very valid category with a material expert score of 86.67%, media 93.33%, and language 90%. Student responses showed a practicality level of 72.72% (practical), while learning outcomes obtained an average of 0.4174 with a t-test value of 8.92 which showed the effectiveness of the mathematics concept book in helping students understand the concept of spatial geometry contextually. Thus, the developed PBL-based mathematics concept book was declared valid, easy to use, and effective as an alternative teaching material in the mathematics learning process.